Hydrogen Sulfide Protects Renal Grafts Against Prolonged Cold Ischemia–Reperfusion Injury via Specific Mitochondrial Actions. Issue 2 (29th November 2016) - Lobb, I.; Jiang, J.; Lian, D.; Liu, W.; Haig, A.; Saha, M. N.; Torregrossa, R.; Wood, M. E.; Whiteman, M.; Sener, A.
Abstract : Ischemia–reperfusion injury is unavoidably caused by loss and subsequent restoration of blood flow during organ procurement, and prolonged ischemia–reperfusion injury IRI results in increased rates of delayed graft function and early graft loss. The endogenously produced gasotransmitter, hydrogen sulfide (H2 S), is a novel molecule that mitigates hypoxic tissue injury. The current study investigates the protective mitochondrial effects of H2 S during in vivo cold storage and subsequent renal transplantation (RTx) and in vitro cold hypoxic renal injury. Donor allografts from Brown Norway rats treated with University of Wisconsin (UW) solution + H2 S (150 μM NaSH) during prolonged (24‐h) cold (4°C) storage exhibited significantly (p < 0.05) decreased acute necrotic/apoptotic injury and significantly (p < 0.05) improved function and recipient Lewis rat survival compared to UW solution alone. Treatment of rat kidney epithelial cells (NRK‐52E) with the mitochondrial‐targeted H2 S donor, AP39, during in vitro cold hypoxic injury improved the protective capacity of H2 S >1000‐fold compared to similar levels of the nonspecific H2 S donor, GYY4137 and also improved syngraft function and survival following prolonged cold storage compared to UW solution. H2 S treatment mitigates cold IRI–associated renal injury via mitochondrial actions and could represent a novel therapeutic strategy to minimize the detrimental clinical outcomes of prolonged cold IRI during RTx. Abstract : This study characterizes the protective effects for renal allografts conferred by hydrogen sulfide treatment during prolonged cold storage, and identifies mitochondria as potential sites of action for hydrogen sulfide during renal ischemia–reperfusion injury. See the editorial from Hauet and Thuillier onpage 313 .